Rapid sol–gel synthesis of nanodiamond aerogel. Issue 24 (1st December 2014) - Manandhar, Sandeep; Roder, Paden B.; Hanson, Jennifer L.; Lim, Matthew; Smith, Bennett E.; Mann, Austin; Pauzauskie, Peter J.
Abstract